Chief looks to be collaborative within and outside the campus force. Issue 4 (15th July 2019) - Enos, Gary
Abstract : Chief Mary Ritayik's rise from patrol officer to the top position in the police department at the State University of New York New Paltz was marked by several opportunities arriving unexpectedly over two decades. Arguably the most pivotal one came when a new chief was hired from a municipal department and began to struggle with not having a second in command in the campus police's organizational structure.